STRATEGI KAMPANYE PD PASAR PAKUAN JAYA DALAM MENINGKATKAN ANTUSIASME MASYARAKAT BERBELANJA DI PASAR TRADISIONAL - Eko Sandi Satiyono; Dwi Rini Sovia; Mariana R.A. Siregar (UNIVERSITAS PAKUAN, 2019)
ASBTRACTTraditional market has negative stigma because of its dirty, slum, not maintained, stinky, and many more negative images. The negative stigma hinders customers from shopping at traditional markets. Most of the buyers who come from upper middle class switch over to modern markets, such as supermarket and minimarket, which are more concern with cleanliness and comfortness. The government of Bogor City is also participating on managing traditional market in Bogor City, through PD Pakuan Jaya Market. PD. Pakuan Jaya is a management company that already existed since 2009, simbolized by the launcing of Ayo ke Pasarâ€ campaign program. This is a descriptive qualitative research using SWOT analysis. Data is gained from some interviews with informan and key informan, obervation and library research. As for data analysis, technique is done by data collections, data reduction, data interpretation, and conclusion, also triangulation process using source triangulation. The result from this analysis is Ayo ke Pasarâ€ campaign program from PD Pakuan Jaya Market. Pakuan Jaya Market is on quadrant I (Strength-Opportunity). It shows that this campaign program has a little strength, but has very big opportunity to overcome weaknesses and threats.Keywords: Enthusiasm,Ayo ke Pasarâ€campaign, Pasar Bogor, traditional market. Keywords : Enthusiasm,